1996
DOI: 10.1093/nar/24.10.1963
|View full text |Cite
|
Sign up to set email alerts
|

Use of a pyrimidine nucleoside that functions as a bidentate hydrogen bond donor for the recognition of isolated or contiguous G-C base pairs by oligonucleotide-directed triplex formation

Abstract: Synthesis of the nucleoside building block of the 6-keto derivative of 2'-deoxy-5-methylcytidine (m5oxC) as an analog of an N3-protonated cytosine derivative is described. A series of 15mer oligonucleotides containing either four or six m5oxC residues has been prepared by chemical synthesis. Complexation of the 15 residue oligonucleotides with target 25mer duplexes results in DNA triplexes containing T-A-T and m5oxC-G-C base triplets. When the m5oxC-G-C base triplets are present in sequence positions that alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The less efficient base stacking observed with this analogue is consistent with the observation that this base does not form stable triplexes at blocks of contiguous guanines, even though it does not suffer from the charge repulsion seen with C + and 5Me C + [33]. Surprisingly stable recognition of G-tracts is achieved by alternating this base analogue with 5Me C [33]. More recently it has been shown that 6-oxocytosine forms a more stable triplet when deoxyribose is replaced with a flexible acyclic linker [34].…”
Section: Pyrimidine Analoguessupporting
confidence: 81%
See 3 more Smart Citations
“…The less efficient base stacking observed with this analogue is consistent with the observation that this base does not form stable triplexes at blocks of contiguous guanines, even though it does not suffer from the charge repulsion seen with C + and 5Me C + [33]. Surprisingly stable recognition of G-tracts is achieved by alternating this base analogue with 5Me C [33]. More recently it has been shown that 6-oxocytosine forms a more stable triplet when deoxyribose is replaced with a flexible acyclic linker [34].…”
Section: Pyrimidine Analoguessupporting
confidence: 81%
“…This could reflect the importance of the positive charge noted above, affecting the energetics of base stacking, or might be due to changes in the hydrogen bonding characteristics since the natural bases form one hydrogen bond with a charged partner in contrast to the uncharged partner with the synthetic base. The less efficient base stacking observed with this analogue is consistent with the observation that this base does not form stable triplexes at blocks of contiguous guanines, even though it does not suffer from the charge repulsion seen with C + and 5Me C + [33]. Surprisingly stable recognition of G-tracts is achieved by alternating this base analogue with 5Me C [33].…”
Section: Pyrimidine Analoguessupporting
confidence: 80%
See 2 more Smart Citations
“…We then examined the formation of triplexes with oligonucleotides containing 15 base pairs with multiple incorporations of the modified nucleosides, both involving either a consecutive run of noncanonical residues or those following an alternating scheme. The target duplexes 17 · 18 and 19 · 20 shown in Table 3 follow the same sequence which has been already used by McLaughlin and co-workers [37]. The third strands containing the dCH + · dG · dC motif is expected to bind in parallel orientation to the target duplex by Hoogsteen base pairing.…”
mentioning
confidence: 99%